ADAPTASI SPASIAL PADA RUMAH TINGGAL PASIEN ISOLASI MANDIRI COVID-19 DI KOTA SEMARANG - Ardiana Yuli Puspitasari; Wa Ode Sitti Khasanah Ramli; Agus Rochani (Universitas Islam Sultan Agung Semarang, 2022)
The Covid-19 pandemic that has hit Indonesia since March 2020 to this day is still a frightening specter. Based on data released from the official website of the Central Java Provincial Government (https://corona.jatengprov.go.id/), until August 4, 2021, Semarang City was still the area with the highest number of cases in Central Java. The higher the number of positive cases is directly proportional to the number of patients who have to be hospitalized. However, with the limited facilities available, it is not possible to accommodate all patients in the hospital. Then the government issued an independent policy at home for patients with mild infections. Self-isolation is not always easy. The potential for distribution to other residents who live in the same house is also quite large if self-isolation is not carried out with strict and correct protocols. The use of shared spaces is also very risky for the potential for virus transmission, for example bathrooms/WCs, kitchens, dining rooms, and bedrooms occupied by more than one person. This phenomenon forces the occupants of the house to adapt. The purpose of this study was to find forms of spatial adaptation in COVID-19 self-isolation residential homes in the city of Semarang. Using qualitative research methods with a rationalistic approach, as well as qualitative descriptive analysis techniques and behavioral mapping. Respondents were determined using a purposive sampling technique with 4 criteria. From this study, it was found that adaptation to space in self-isolated residences in Semarang City is convertibility to change the function of space, with the recommended minimum space requirements for people when they want to build a house are 2 bathrooms, laundry room outside the house, 2 separate accesses. to enter and leave the house, and voids that receive direct morning light.